A new species of Leptolalax (Anura: Megophryidae) from the western Langbian Plateau, southern Vietnam - Poyarkov, Nikolay Jr. A. (Zootaxa, 2015)
We describe a new species of megophryid frog from Loc Bac forest in the western part of the Langbian Plateau in the southern Annamite Mountains, Vietnam. Leptolalax pyrrhops sp. nov. is distinguished from its congeners by a combination of the following morphological attributes: (1) presence of distinct dark brown/black dorsolateral markings, including blackish spots on flanks and dark canthal and/or temporal streaks; (2) rudimentary webbing on toes; (3) tympanum externally distinct; (4) dorsal skin finely shagreened with numerous small tubercles and pustules; (5) medium size for the genus (30.3–33.9 mm in 2 adult males, 30.8–34.3 mm in 7 females); (6) grey-pinkish to dark brownish-violet chest and belly with numerous whitish speckles, also covering the lateral sides of body; (7) ventrolateral glands small, indistinct, do not form a distinct line; (8) pectoral glands comparatively small, comprising 1–3% of adult SVL; (10) iris bicolored, typically bright orange-red in upper two-thirds, fading to silvery green in lower third. The male advertisement call of the new species is also unique among those Leptolalax species for which calls are known, with a single long ’introductory’ note, consisting of 5–12 pulses, followed by of 4–5 predominantly single-pulsed notes, and an average dominant frequency of 1.91–2.23 kHz. From the morphologically similar L. applebyi, L. melicus and L. bidoupensis, Leptolalax pyrrhops sp. nov. can be further distinguished by 13.5%, 13.7% and 10.3% sequence divergence at the 16S rRNA mtDNA gene. At present, the new species is known from montane evergreen forest between 800–1100 m elevation. We suggest the species should be considered as Data Deficient following IUCN’s Red List categories. To date our finding represents the southernmost known record of the genus Leptolalax from Vietnam.